PENERAPAN PENDEKATAN REBT (RASIONAL EMOTIVE BEHAVIOR THERAPHY) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Laras Melinda Yanti; Salsabila Maharani Saputra (IKIP Siliwangi, 2018)
The Rational Emotive Behavior Therapy (REBT) approach is a view based on humans, which explains that individuals have a tendency to think irrationally, one of which is obtained through social learning. Rational Emotive Behavior Therapy (REBT) aims to eliminate emotional disorders that can damage the individual's self such as anxiety, hate, fear, feeling troubled, angry, and so on. One factor that influences student / student achievement is motivation. With the motivation, students / students will study harder, resilient, persevering and have full concentration in the learning or learning process. Motivation to learn is one of the things that needs to be raised in the learning effort at school. Rational Emotive Behavior Therapy (REBT) approach to increase learning motivation is an effort in providing assistance to students / students to be able to optimize and develop the potential possessed by students / students. Thus, conclusions can be drawn about the